Nanozymes for Accelerating the Foot Wound Healing: A Review - Lv K; Zhang S; Yao Z; Zhou C; Xu J (International Journal of Nanomedicine)
Ke Lv,1,* Shumin Zhang,2,* Zimo Yao,3,* Chao Zhou,2 Jianda Xu1 1Department of Orthopaedics, Changzhou Hospital Affiliated to Nanjing University of Chinese Medicine, Changzhou, Jiangsu Province, People’s Republic of China; 2School of Medical and Health Engineering, Changzhou University, Changzhou, Jiangsu Province, People’s Republic of China; 3The Fourth Clinical School of Nanjing Medical University, Nanjing City, Jiangsu Province, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jianda Xu, Department of Orthopaedics, Changzhou hospital affiliated to Nanjing University of Chinese Medicine, 25 North Heping Road, Changzhou, Jiangsu Province, 213003, People’s Republic of China, Email milidoc3@163.com Chao Zhou, School of Medical and Health Engineering, Changzhou University, Changzhou, Jiangsu Province, 213164, People’s Republic of China, Email zhouchao@cczu.edu.cnAbstract: Diabetic foot is a most common and life-threatening complication of diabetes. It often results in a protracted course of wound healing. Currently, treatments for diabetic foot include wound dressings, antibiotics, and debridement. However, these treatments are often inadequate due to the complexity of diabetic foot. Various adjuvant therapies are currently under investigation to accelerate wound healing. In recent years, the emergence of nanozymes, nanomaterial with natural enzyme-like characteristics and activities, have attracted much attention. As a promising candidate in biomedicine, the breadth of application is growing fast, with different mechanisms for accelerating wound healing, such as antioxidant effects, antibacterial effects, promotion of angiogenesis, and regulation of the wound microenvironment. Faced with the inherent defects of nanozyme, new multifunctional nanozymes composite materials have also been continuously developed to achieve synergistic effects with various types of enzymatic activities. This is a new strategy for diabetic foot wound healing in the future. This review summarizes current knowledge about nanozymes and their potential mechanisms in diabetic wound healing. An overview of progress in the applied research on these nanozymes, current challenges and future perspectives of nanozymes in related fields of diabetic wound healing is also discussed to stimulate new strategies and preclinical translations.Keywords: nanozymes, diabetic foot, wound, healing, therapy